Good outcomes of modified Grammont and Langenskiöld technique in children with habitual patellar dislocation - Musielak, Bartosz Jan (Knee Surg Sports Traumatol Arthrosc, 2020)
PURPOSE: In this study, the functional mid-term outcomes of the modified Grammont and Langenskiöld technique was assessed in skeletally immature patients with habitual patellar dislocation, with emphasis on knee function, pain, and other possible post-surgical complications. This is the first study concerning the application of the modified Grammont and Langenskiöld technique in habitual patellar dislocations. METHODS: This retrospective cohort study considered 10 patients (15 knees), ranging from 7 to 11 years old, who underwent the modified Grammont and Langenskiold procedure between 2015 and 2018. History of dislocation, patellar stability and range of motion (ROM) were analysed. To assess functional improvement and knee pain, the Kujala Anterior Knee Pain Scale and KOOS-Child Knee Survey were used before and after surgical treatment. RESULTS: No history of dislocation was noted after surgical treatment. All 15 knees showed full ROM. There were no signs of genu recurvatum and no length discrepancies were found. The subjective assessment revealed significant improvement in the scores of the KOOS-Child questionnaire in all five sections (p < 0.001), as well as in The Kujala Anterior Knee Pain Scale (p = 0.001). CONCLUSION: The modified Grammont and Langenskiöld technique yields remarkable results in terms of knee stability and knee function, while decreasing recurrence risk and intensity of pain in patients with challenging cases of patellofemoral joint dislocation. This surgical technique is most effective in cases where the patella remains dislocated continuously; however, it may also be used in immature patients with recurrent instability. LEVEL OF EVIDENCE: IV.